THE EFFECTIVENESS OF WORKSHEET-ASSISTED PROBING PROMPTING LEARNING MODEL ON STUDENTS’ CRITICAL THINKING SKILLS IN THE SUBJECT OF REACTION RATE AT MAS ULUMUDDIN LHOKSEUMAWE - Pocut Intan; Riska Imanda; Sirry Alvina (Chimica Didactica Acta, 2021)
This study aimed to determine the differences in critical thinking skills (CTS) between classes using the worksheet-assisted probing prompting learning model and those using only probing prompting learning model for the subject of reaction rate at MAS Ulumuddin Lhokseumawe. The research method was quasi-experimental with the Nonequivalent Control Group research design. The sample used were two classes with 30 students in each. The data was collected by using multiple choice test questions. The results showed that there were differences in the critical thinking skills of students who were taught using the worksheet-assisted probing prompting learning model and students who were taught with only probing prompting learning model. Since there was a significant value of 0.000 0.05, then the Ha was accepted while the H0 was rejected. It can be concluded that there is a significant effect of the probing prompting learning model assisted with students’ worksheet on the critical thinking skills of students at MAS Ulumuddin Lhokseumawe.